Microflora Influence: The Aquatic Environment Changes Grouping Risk and Development Speed of Toad Tadpoles - Hase, Kazuko (Frontiers in Ecology and Evolution, 2022)
In addition to habitat loss and fragmentation, behavioral traits and the deterioration of water environments also contribute to the local extinction of amphibians. Abundant microflora in urban ponds may cause fatal diseases, whereas symbiotic bacteria may protect the host from pathogens; these effects may vary with group size. In this study, I monitored the growth of Japanese common toad (Bufo japonicus) larvae in Tokyo using three different group sizes: 1 (solitary), 2 (pair), and 15. Although there was no genetic bias in the major histocompatibility complex (MHC) class II genes or microsatellite loci to the survival of the larvae, the mortality risk of the larvae reared in pond water was higher than that of those reared in tap water. According to the survival analysis, the risk was more significant when the group size was 15. This result would be unwelcomed for the B. japonicus tadpoles, which have habits of social aggregation. Furthermore, larval metamorphosis took longer to complete in pond than tap water without any difference in body length or mass. These findings provide fundamental insight into the impact of the aquatic environment and the effect of the group size on animal health and conservation.